Public policy praxis : a case approach for understanding policy analysis - Clemons, Randall S.; McBeth, Mark K. (New York, NY : Routledge, 2021)
"Public administration and policy analysis education have long emphasized tidiness, stages, and rationality, but practitioners frequently must deal with a world where objectivity is buffeted by, repressed by, and sometimes defeated by value conflict. Politics and policy are "messy" and power explains much more about the policy process than does rationality. Public Policy Praxis, now in a thoroughly revised fourth edition, uniquely equips students to better grapple with ambiguity and complexity. By emphasizing mixed methodologies, the reader is encouraged, through the use of a wide variety of policy cases, to develop a workable and practical model of applied policy analysis. Students are given the opportunity to try out these globally applicable analytical models and tools in varied case settings (e.g., county, city, federal, international, plus urban and rural) while facing wide-ranging topics (starving farmers and the red panda in Nepal, e-cigarettes, GMOs, the gig economy, and opioid abuse) that capture the diversity and reality of public policy analysis and the intergovernmental and complex nature of politics. The fourth edition expands upon its thorough exploration of specific tools of policy analysis, such as stakeholder mapping, content analysis, group facilitation, narrative analysis, cost-benefit analysis, futuring, and survey analysis. Along with teaching "how to," the authors discuss the limitations, the practical political problems, and the ethical problems associated with different techniques and methodologies. Many new cases have been added, along with clear instructions on how to do congressional research and a Google Trends analysis. An expanded online Teaching Appendix is included for adopters, offering original cases, answers to problems, alternative approaches to case use, teaching exercises, student assignments, pedagogical ideas, and supplemental material directly tied to concepts covered in the text. With an easily accessible and conversational writing style, Public Policy Praxis is an ideal textbook for undergraduate and graduate courses in public policy analysis, community planning, leadership, social welfare policy, educational policy, family policy, and special seminars"--
OCLC-licensed vendor bibliographic record.
Keywords: Policy sciences; Policy sciences -- Case studies; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Affairs & Administration